(untitled) (Circe de clásicos y modernos, 2024)
The notion of natural theology is a key one in the work of Augustine who, as a Roman formed from the coordinates of the classical canon, builds within his work the necessary devices to give legitimate, although partial, entry to Greco-Roman elements that will be guide his own argument in the territory of Christian literature. The eighth book of his treatise The City of God allows us to observe the extraction of that notion from its area of origin, especially the texts of Varro and Cicero, which in turn have their antecedents in the academic and Stoic philosophical tradition, their adaptation to the horizon of biblical-Christian meaning and its interested use within it. The operation carried out by Augustine gives us a glimpse of his knowledge and ability to manipulate the Roman-Republican literary tradition, in addition to certain conceptions from the doxographic vulgate in force in his context, such as those of “schools” and philosophical “successions.” We are interested in focusing, above all, on the games of amalgamations and semantic shifts that Augustine rehearses on the profile of Socrates, with very specific purposes, and which lead us to observe, also, the circulation of ideas in the North African Roman area, for which we have some interesting antecedents, such as the Latin apologetics books of Tertullian and Minutius Felix, between the 2nd and 3rd centuries.